2022
DOI: 10.1021/acsnano.2c06666
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Covered Nanocarriers for Targeted Delivery of Hirudin to Eliminate Thrombotic Complication in Tumor Therapy

Abstract: Most patients are at high risk of thrombosis during cancer treatment. However, the major discrepancy in the therapeutic mechanisms and microenvironment between tumors and thrombosis makes it challenging for a panacea to treat cancer while being able to eliminate the risk of thrombosis. Herein, we developed a biomimetic MnOx/Ag2S nanoflower platform with platelet membrane modification (MnOx@Ag2S@hirudin@platelet membrane: MAHP) for the long-term release of anticoagulant drugs to treat thrombosis together with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The photothermal efficiency of the metasurface before and after the infiltration with NOA 61 can be estimated based on the time constant value (τ). Such an approach is validated in the Roper model and is widely accepted for assessing the photothermal efficiency of new materials, as τ is inversely proportional to the photothermal efficiency. The calculated values of τ before and after the infiltration with NOA 61 were 34 and 42 s, respectively (see the Supporting Information for more details).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The photothermal efficiency of the metasurface before and after the infiltration with NOA 61 can be estimated based on the time constant value (τ). Such an approach is validated in the Roper model and is widely accepted for assessing the photothermal efficiency of new materials, as τ is inversely proportional to the photothermal efficiency. The calculated values of τ before and after the infiltration with NOA 61 were 34 and 42 s, respectively (see the Supporting Information for more details).…”
Section: Results and Discussionmentioning
confidence: 99%
“…81,82 Integrin GPIIb-IIa on the surface of platelets binds to fibrinogen and aggregates at the site of damaged blood vessels to form a thrombosis. 83,84 In addition, platelets have strong binding ability to blood clots and type IV collagen, which can target damaged blood vessels at tumor sites. 85 Recent studies have shown that Pselectin on platelets specifically binds to the CD44 receptor overexpressed on tumor cells.…”
Section: Biomimetic Nanoparticles Functionalized By Different Kinds O...mentioning
confidence: 99%
“…In addition, living cell-based nanomaterials can be combined with advanced biofabrication techniques, such as three-dimensional (3D) bioprinting and microfluidics, which have great potential for tissue engineering applications. To this end, various living cells, such as mesenchymal stem cells, [278,279] neural stem cells, [280][281][282][283] dental-pulp stem cells, [284] adipose-derived stem cells, [285] erythrocytes, [136,286,287] leukocytes, [288] NK cells, [289] monocytes, [290,291] macrophages, [62,[292][293][294][295][296][297] neutrophils, [63,[298][299][300] lymphocytes, [301] DCs, [302] and platelets, [303,304] have been exploited to engineer nanomaterials, which is the second type of CCT. Such cellularized nanomaterials have demonstrated great potential as "Trojan horses" for active targeting and therapy of various diseases.…”
Section: Passive Nanoparticles Cloaked With Living Cellsmentioning
confidence: 99%